Kurdish ethnic identity in the Middle Ages - Hassan, Prof.Dr.Qader Mohammed; Ali, Prof. Kaban Abdulkarim Sheikh (Sulaimani Journal for Humanities, 2025)
The issue of Kurdish historical identity and the consequences associated with this identity and its framework in the Middle Ages is an important field of research in the identity of a nation that appeared for the first time in history The Kurdish ancestry and the historical information about their origin are one of the most obvious components of Kurdish identity from the perspective of the other non-Kurdish, especially Arabs and Persians. This research is mainly devoted to discussing the dimension of origin and its impact on the formation of others' attitudes and views about Kurds and their identity. This study academically discusses the Kurdish origin as the most important pillar of independent identity, based on the narratives in Islamic sources, despite the changes in the discourse of Islamic historians about the Kurdish origin and considering them as a nation with characteristics Gore, especially the Shiite view, whose historical and jurisprudence sources have regarded the issue as a special subject.